Моделирование тонкоплёночного солнечного элемента на основе гетероструктуры Cu(In,Ga)Se2/CdS - Сребнюк, Е. А.; Галат, А. Б. (ХНУРЕ, 2019)
Article describes an algorithm and its software realization in SCAPS for numerical simulation and optimization of parameters (layer thickness, layer configuration etc) of Cu(In,Ga)Se2/CdS hetero-junction thin film solar cell, allowing to plot I-V, C-V curves, calculate current, ETA % and many other parameters based on different variables [3].
Keywords: Моделирование тонкоплёночного солнечного элемента; гетероструктуры Cu(In,Ga)Se2/CdS